Pengaruh PENGARUH INTERVAL TRAINING DALAM MENINGKATKAN VO2MAX PADA ATLET REMAJA PENCAK SILAT DIPERGURUAN NURHATI HST - Rizky, Ahmad; Arifin, Syamsul; Mulhim, M. (Universitas Hamzanwadi, 2025)
The main problem is low vo₂max capacity, which causes early fatigue and a significant decline in performance at the end of the game, thereby impacting achievement. This study aims to determine the effect of interval training on increasing the vo₂max of these adolescent athletes. The method used was an experiment with a one-group pretest-posttest design. The research population consisted of 24 athletes, with a sample of 10 adolescent athletes selected through purposive sampling. The instrument used to measure vo₂max was the multistage fitness test or bleep test. Data analysis techniques included normality tests, homogeneity tests, and paired sample t-tests. The results showed an average increase in vo₂max of 3.16 mL/kg/minute, from 36.95 mL/kg/minute (fair/poor category) to 40.11 mL/kg/minute (fair/good category), with a t-test significance value of less than 0.08. The discussion confirmed that interval training for 16 sessions effectively stimulated an increase in the efficiency of the oxygen transport system and cardiorespiratory endurance in adolescents. The conclusion of the study proved that interval training has a significant and effective influence on increasing vo₂max, so it can be integrated into physical training programs to improve the stamina and competitive performance of adolescent pencak silat athletes.